Circulating gluten‐specific, but not CMV‐specific, CD39+ regulatory T cells have an oligoclonal TCR repertoire. Issue 1 (12th January 2020) - Cook, Laura; Munier, C Mee Ling; Seddiki, Nabila; Hardy, Melinda Y; Anderson, Robert P; Zaunders, John; Tye‐Din, Jason A; Kelleher, Anthony D; van Bockel, David
Abstract: Objectives: Understanding the T cell receptor (TCR) repertoire of regulatory CD4 + T‐cell (Treg) populations is important for strategies aiming to re‐establish tolerance in autoimmune diseases. We studied circulating deamidated gluten‐epitope‐specific CD39 + Tregs in patients with coeliac disease following an oral gluten challenge, and we used cytomegalovirus (CMV)‐specific CD39 + Tregs from healthy controls as a comparator population. Methods: We used the OX40 assay to isolate antigen‐specific Tregs by induced surface co‐expression of CD25, OX40 and CD39. RACE PCR amplification and Sanger sequencing of the TCR β chain were used to analyse repertoire diversity. Results: We found that, following oral gluten challenge, circulating gluten‐specific CD39 + Tregs had an oligoclonal TCR repertoire that contained public clonotypes. Conversely, the TCR repertoire of CMV‐epitope‐specific CD39 + Tregs from healthy controls was polyclonal. Discussion: These data indicate that a biased TCR repertoire is not inherent to CD39 + Tregs, and, in this case, is apparently driven by the HLA‐DQ2.5‐restricted deamidated gluten peptide in coeliac disease patients. Conclusion: This is the first assessment of the TCR repertoire within circulating human Tregs specific for foreign antigen. These data enhance our understanding of antigen‐specific CD4 + responses in the settings of chronic inflammation and infection and may help guide immunomonitoring strategies for CD4 + T cell‐based therapies, particularly for coeliac disease. Abstract : Coeliac disease results from a loss of tolerance toward dietary gluten driven by pathogenic CD4 + T cells. We have previously shown gluten‐specific CD39 + Tregs are functionally impaired in patients. Here we show this Treg population has an oligoclonal TCR repertoire; however, this is not a general feature of peripheral Tregs as responses to CMV peptides contained a polyclonal TCR repertoire.